Aksiologi Ilmu Pengetahuan Manajemen Pendidikan Islam - Didin Sirojudin; Hilyah Ashoumi (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2020)
Value always manifests together in actions or actions carried out by humans whenever and wherever humans have needs, although it cannot be denied that sometimes the context of values ??is mostly wrapped in dialogical and dialectical uses of simple language which is difficult to philosophize. The problem is whether we are aware of it or not? actually we are discussing a value ?. Questioning the benchmarks regarding the value, situation and status of the value, investigating the statement of an object and other possibilities related to the nature of value. Research on the axiology of Islamic education management science, the author examined using the library method or literature review, the goal is that the orientation of the values ??expected from the implementation of Islamic education management science can be known for its definition and benefits. The results of this study are the orientation of the values ??expected from the implementation of Islamic education management science itself is to embed leadership, managerial and organizational values ??into a personal soul that is stable, dynamic, independent and creative, so that in action it is always based on tangible Islamic characters. in several values, namely the value of worship, the value of benefit, the value of mercy (affection), the value of goodness, the value of long-term orientation, and submission to God.